Of Parachutes and Participant Protection: Moving Beyond Quality to Advance Effective Research Ethics Oversight. (July 2019) - Lynch, Holly Fernandez; Nicholls, Stuart; Meyer, Michelle N.; Taylor, Holly A.; ,
There are several reasons to believe that Institutional Review Boards (IRBs) and Human Research Protection Programs (HRPPs) contribute to ethical research and the protection of research participants, but there are also important reasons to interrogate this belief. Determining whether IRBs and HRPPs "work" requires empirical evaluation of whether and how well they actually achieve what they were designed to do. In other words, it is critical to examine their outcomes and not only their procedures and structures. In this response to Tsan, we argue that the concept of IRB and HRPP quality entails three dimensions: (1) effectiveness, (2) procedures and structures likely to promote effectiveness, and (3) features unrelated to effectiveness but nonetheless essential, such as efficiency, fairness, and proportionality. Because not all types of quality necessarily guarantee or entail effectiveness, we suggest that broad quality assessments, including such features as regulatory compliance and other procedural measures suggested by Tsan, are unhelpful as the first step in evaluating IRBs and HRPPs. Instead, we must start with outcomes relevant to effectiveness. To do this, we launched the Consortium to Advance Effective Research Ethics Oversight (AEREO), with a mission to define and specify ways to measure relevant outcomes for research ethics oversight, empirically evaluate whether those outcomes are achieved, test new approaches to achieving them, and ultimately, develop and implement empirically-based policy and practice to advance IRB and HRPP effectiveness. We describe several anticipated AEREO projects and call for collaboration between various stakeholders to more meaningfully evaluate IRB and HRPPs.